Development Of A Pin Diode-Based Beam-Switching Single-Layer Reflectarray Antenna - Abbasi, Muhammad Inam; Ismail, Muhammad Yusof; Kamarudin, Muhammad Ramlee (Hindawi Limited, 2020)
*is paper presents a practical demonstration for the design and development of a switchable planar reflectarray using PIN diodes in the X-band frequency range. Waveguide scattering parameter measurements for the unit cells and far-field measurements of the periodic reflectarrays have been carried out to verify the predicted results. Reflectarray unit cell measurements demonstrated a frequency tunability of 0.36 GHz with a dynamic phase range of 226°. On the other hand, the designed 6 × 6 periodic reflectarray has been shown to achieve beam switching from +6° to −6° with different switching states of PIN diodes. *is type of beam switching can be used in satellite communication for specific region coverage.